Taufiq Al-Hakim’s World View on Social Justice in the Short Story Daulah Al-Ashafir: A Sociological Analysis of Lucien Goldmann’s Literature - Nurmaulidiva, Violentia Wahyu (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study explores the worldview (vision du monde) of Taufiq Al-Hakim regarding social justice through a literary sociology analysis of the fable short story Daulah al-Ashafir. The main issue addressed is the disparity between the ideal egalitarian order of bird society and the moral decadence of human society dominated by greed (al-jashā‘). By employing the Genetic Structuralism theory of Lucien Goldmann, this study examines the dialectical relationship between the structure of the text and the social structure of the author’s society. The method used is descriptive qualitative with a content analysis approach, linking literary texts as products of a collective subject to the socio-historical reality of Egypt. The findings indicate that Taufiq Al-Hakim uses the analogy of sparrows as a symbol of a social group that upholds the values of hard work and solidarity, while simultaneously serving as a sharp satire of the exploitative culture of human society. The conclusion of this study affirms that social justice, in Al-Hakim’s perspective, cannot be achieved solely through material systems, but must begin with the liberation of individuals from the constraints of materialism and greed, which hinder social harmony. This study contributes to the enrichment of contemporary Arabic literary sociology through the deconstruction of fable symbolism.